Teaching Trauma-Informed Care: A Symposium for Medical Students - Binny Chokshi; Kimberly Walsh; Danielle Dooley; Olanrewaju Falusi; Lawrence Deyton; Lee Beers (Association of American Medical Colleges, 2020)
Introduction A large body of evidence links exposure to childhood trauma with negative health outcomes. Training future physicians to recognize and respond to trauma is paramount, and engaging medical students in the preclinical years affords the opportunity to foster the development of a trauma-informed lens that can then be solidified during clinical clerkships. Methods We developed and implemented a 4-hour trauma-informed care (TIC) symposium for 179 second-year medical students at the George Washington University School of Medicine and Health Sciences during the Patients, Populations, and Systems course. The symposium included three interactive didactic sessions focusing on the connection between trauma and health and TIC principles. A facilitated small-group discussion allowed students to apply TIC principles to a patient case, followed by reflection and evaluation. Results The overall rating of the TIC symposium was 4 out of 5. Strengths included integration of a small-group case with discussion on application of TIC in practice, experience of the lecturers and small-group facilitators, and review of research relating adversity to specific health outcomes. Suggestions for improvement included incorporating role-play and standardized patients. Content analysis of student reflections mapped to the domains of physician competency. Discussion A 4-hour symposium can affect student knowledge and understanding of TIC. Teaching TIC presents an opportunity to prepare medical students for a career in medicine through cultivation of required physician competencies. Next steps include enhanced opportunities to practice TIC and follow-up analysis of participants to determine behavior change during clinical years.